Analisis Kemampuan Literasi Baca Tulis Siswa Kelas V Dalam Menyelesaikan Soal Asesmen Kompetensi Minimum - Tressa Linanda; Deri Hendriawan (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The National Assessment is a new government policy related to the initial system of school quality mapping. The National Assessment consists of a Minimum Competency Assessment, a Character Survey and a Learning Environment Survey. This policy change was based on the low PISA results obtained by the Indonesian state. As a step to improve Program for International Student Assessment (PISA) scores, the Minimum Policy Assessment Program is based on collaboration between PISA and Trends in International Mathematics and Science Study (TIMSS) with the aim of improving literacy skills, namely reasoning using language, improving numeracy or mathematics and improve character education in students. Literacy skills in AKM consist of informational text content and fictional texts by emphasizing students to be able to understand, evaluate, and reflect on texts on questions with the aim of developing individuals to be able to develop themselves optimally as Indonesian citizens. The location of this research was carried out by SD Negeri Lialang with the aim of identifying the reading literacy skills of fifth grade students in solving Minimum Competency Assessment simulation questions. The research approach used is a qualitative approach with content analysis methods. The subjects in this study were the researchers themselves. The object of the research is a simulation test sheet for class V students as many as 30 students. Data collection was carried out in this study using tests, interviews and documentation. The literacy ability of class V students got the results that from 30 students, as many as 20 students or 66.67% were in moderate ability.